2011
DOI: 10.1093/jnci/djr216
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Circulating Interleukin 6, Interleukin 8, C-Reactive Protein, and Risk of Lung Cancer

Abstract: Although increased levels of both serum IL-6 and IL-8 are associated with lung cancer, only IL-8 levels are associated with lung cancer risk several years before diagnosis. Combination of IL-8 and CRP are more robust biomarkers than either marker alone in predicting subsequent lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
236
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(258 citation statements)
references
References 39 publications
17
236
3
2
Order By: Relevance
“…SNPs located in the promoter region of IL-6 can alter gene transcription, thereby affecting the serum level of the cytokine. A cytosine-to-guanine mutation in IL-6 at position -174 has been identified and the G allele has been confirmed to be related to multiple diseases, including cancer (Pine et al, 2011) Several studies have indicated that IL-6 level is related to lung cancer prognosis (Cox et al, 2001). However, to our knowledge, this is the first study to explore the association between the IL-6 -174G/C gene polymorphism in the promoter region and NSCLC prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…SNPs located in the promoter region of IL-6 can alter gene transcription, thereby affecting the serum level of the cytokine. A cytosine-to-guanine mutation in IL-6 at position -174 has been identified and the G allele has been confirmed to be related to multiple diseases, including cancer (Pine et al, 2011) Several studies have indicated that IL-6 level is related to lung cancer prognosis (Cox et al, 2001). However, to our knowledge, this is the first study to explore the association between the IL-6 -174G/C gene polymorphism in the promoter region and NSCLC prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…Immunologic studies suggest that the downstream kynurenines may serve as a feedback of TH1 cell suppression and enhance TH2 response (24). Indeed, inflammation biomarkers have previously been strongly associated with lung cancer risk, indicating that inflammatory processes may be important in early lung cancer pathogenesis (28,29). It would be useful to obtain measurement of inflammation biomarkers, such as C-reactive protein, to further evaluate whether these associations are linked to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, most case-control studies have shown a higher cancer risk in people with elevated CRP levels (Gunter et al, 2006;Helzlsouer et al, 2006;Otani et al, 2006;Aleksandrova et al, 2010;Chaturvedi et al, 2010;Lee et al, 2011;Pine et al, 2011), while, the findings from prospective cohort studies have been inconsistent (Il'Yasova et al, 2005;Zhang et al, 2005;Siemes et al, 2006;Zhang et al, 2007;Allin et al, 2009;Heikkila et al, 2009;Pierce et al, 2009;Dos et al, 2010;Prizment et al, 2011;Van et al, 2011).…”
Section: Association Between C-reactive Protein and Risk Of Cancer: Amentioning
confidence: 99%